Do racional ao irracional: um sequência didática para a construção do conjunto dos números reais no ensino básico - Faifer, Isabel Roncato (2023)
Faced with the current scenario of education, where the teaching of mathematics takes place, each day more, in a mechanical way and far from critical thinking, the present work approaches a proposal for the use of the history of mathematics as a teaching methodology for the introduction of the content of irrational numbers and construction of the set of real numbers, based on reflections and discussions about the notion of infinity, for a ninth grade elementary school class, with the aim of building a meaningful teaching and learning process for students.